Tremellafuciformis polysaccharides inhibit UVA‐induced photodamage of human dermal fibroblast cells by activating up‐regulating Nrf2/Keap1 pathways. (25th March 2021) - Fu, Hao; You, ShiQuan; Zhao, Dan; An, Quan; Zhang, Jiachan; Wang, Changtao; Wang, Dongdong; Li, Meng
Abstract: Background: UVA radiation can cause skin oxidative stress. Tremella fuciformis polysaccharides (TFPS) are the main active ingredient in Tremella. Previous studies have shown that TFPS have protective effects on UVA‐induced oxidative stress cells, but the specific protective mechanism has not been clarified. Objective: This study aims to explore the potential protective mechanism of Tremella fuciformis polysaccharides on UVA‐induced damage to human dermal fibroblasts cells. Methods: We evaluated the protective ability of TFPS against UVA‐induced damage by detecting cell survival rate, the content of reactive oxygen species (ROS) and malondialdehyde (MDA) in the cells, and the scavenging activity of ABTS free radicals, as well as the enzyme activity of superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GSH‐Px), and the Nrf2‐Keap‐1 pathway protein and gene were measured to study the protective mechanism of TFPS from photodamage. Results: TFPS pretreatment can reduce the oxidative stress of UVA‐treated human dermal fibroblasts cells. After TFPS pretreatment, the content of ROS and MDA in the cell decreased significantly and the total antioxidant activity was increased. Among them, the active of CAT, SOD, and GSH‐Px in the cells increased significantly. TFPS can also protect fibroblasts by up‐regulating Nrf2 and down‐regulating Keap1 expression. Finally, it was also found that TFPS pretreatment increased the content of collagen I, elastin, and hyaluronic acid (HA) in skin fibroblasts treated with UVA. Conclusion: These results indicate that a certain concentration of TFPS can effectively alleviate skin damage caused by UVA, and they may be used as an effective component of cosmetics.